Vertical Equity, Adequacy and Wisconsin School Finance Policy - Deborah A. Verstegen (Educational Considerations, 2002)
The Wisconsin Constitution, adopted in 1848, provides that “The legislature shall provide by law for the establishment of district schools, which shall be as nearly as uniform as practicable.” For over 150 years the legislature has grappled with the question of how to achieve this mandate, particularly as social, economic and demographic changes have conditioned concepts of what is “as nearly as uniform as practicable..."